Padlet-Based Collaborative Writing: Enhancing EFL Students’ Paragraph Coherence and Engagement - Yusak Suharno; Testiana Deni Wijayatiningsih; Eko Andy Purnomo; Raqib Chowdhury (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2026)
This current research scrutinized the implementation of collaborative writing on Padlet to enhance students' coherence in writing paragraph and their engagement in the learning process. This current research employed a quasi-experimental one-group pretest-posttest design and a descriptive qualitative approach to examine students' learning processes and interactions. Twenty-five first-year college students at one of the private universities in Indonesia who joined a writing paragraphs course. Quantitative data were gathered via paragraph-writing assessments and analyzed using paired-samples t-tests, whilst qualitative data were collected through observations, questionnaires, and student reflections. According to the study, students' paragraph coherence greatly improved, with mean scores rising from 68.40 to 81.24 (p < 0.05). Additionally, throughout the six-week intervention, engagement data showed a significant shift toward more content-focused peer criticism, as well as increased participation in posting, commenting, and editing activities. The results show that lines written in groups on Padlet are easier to understand and that students are more interested in writing in English as a second language. However, since this study employed a one-group design without a control group, the findings should be interpreted cautiously. Future studies are needed to further the effectiveness of Padlet-based collaborative writing in improving students’ coherence and engagement through more rigorous experimental designs.